2005
DOI: 10.1007/s10646-004-6370-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Organic Compounds to Marine Invertebrate Embryos and Larvae: A Comparison Between the Sea Urchin Embryogenesis Bioassay and Alternative Test Species

Abstract: This study investigated the toxic effects of the insecticides lindane and chlorpyrifos, the herbicide diuron, the organometallic antifoulant tributyltin (TBT), and the surfactant sodium dodecyl sulfate (SDS) on the early life stages of Paracentrotus lividus (Echinodermata, Euechinoidea), Ciona intestinalis (Chordata, Ascidiacea), Maja squinado and Palaemon serratus (Arthropoda, Crustacea) in laboratory acute toxicity tests. The assays studied embryogenesis success from fertilized egg to normal larvae in P. liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 76 publications
7
63
0
7
Order By: Relevance
“…This supports the hypothesis that TBT and DBT enter organisms through diffusion at pH 8 [12], because the two BTs exclusively exist as the neutral species at that pH (Supplemental Data, Table S1). Studies have found that some organisms such as Paracentrotus lividus have an EC50 value of 300 ng/L when exposed to TBT, even in artificial seawater with a very high concentration of cations at approximately pH 8 [37]. This also indicates that TBT can still be extremely toxic to organisms at pH 8, although the hardness is very high; this agrees with the results of the present study.…”
Section: Water Hardness Effect On Toxicity Of Tbt and Dbtsupporting
confidence: 92%
“…This supports the hypothesis that TBT and DBT enter organisms through diffusion at pH 8 [12], because the two BTs exclusively exist as the neutral species at that pH (Supplemental Data, Table S1). Studies have found that some organisms such as Paracentrotus lividus have an EC50 value of 300 ng/L when exposed to TBT, even in artificial seawater with a very high concentration of cations at approximately pH 8 [37]. This also indicates that TBT can still be extremely toxic to organisms at pH 8, although the hardness is very high; this agrees with the results of the present study.…”
Section: Water Hardness Effect On Toxicity Of Tbt and Dbtsupporting
confidence: 92%
“…It also limits cell division in phytoplankton and reproduction of zooplankton. TBT has been reported to induce shell calcification anomalies in the oyster Crassostrea gigs at a level of 2 ng L -1 and to disturb the reproduction of bivalve mollusks at 20 ng L -1 (Bella et al 2005a). Ruiz et al (1995) investigated the effect of TBT exposure on veliger larval development of the bivalve (C. tsubasa).…”
Section: Toxicity To Marine Invertebratesmentioning
confidence: 99%
“…In many marine species, such effects include larval mortality (Bella et al 2005a) and impairment in growth, development, reproduction, and survival (Haggera et al 2005). Moreover, the results of several experiments have indicated that there is or may be a spectrum of potential adverse chronic systemic effects of organotin exposure in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…In tests with elutriates or pore waters, crustaceans, and particularly early life stages, have been found to be several orders of magnitude more sensitive to insecticides than echinoderms and molluscs (Ramamoorthy and Baddaloo, 1995;Bellas et al, 2005). Crustaceans are also particularly sensitive to cadmium (Mariño-Balsa et al, 2000) compared to other marine invertebrates.…”
mentioning
confidence: 99%